Penerapan Metode Earned Value Dalam Analisis Kinerja Biaya Dan Waktu Pada Proyek Konstrusksi Sports Center Smk Bhakti Kartini Kecamatan Rawalumbu, Kota Bekasi - Asa, M. Fanshurullah; Izzathamma, Alditya Riefqi (TheJournalish: Social and Government, 2024)
Sports Center is a place consisting of activities and efforts that can help develop or foster a person's physical and spiritual potentials, whether in the form of games, matches, or just filling free time with sports. The Sports Center of SMK Bhakti Kartini located at Jl. Caringin no. 8, Kec. Rawalumbu, Bekasi City, West Java is one of the large 2-story Sports Centers, with various facilities such as a gymnasium, futsal with an international standard field, basketball, and various other facilities. In the construction of this Sports Center, there were many problems with delays in its construction, therefore a study was needed to analyze cost and time control. One of the project management methods for controlling costs and time is the Earned Value method. The Earned Value method is a method of managing a project by analyzing cost and time performance based on the weight of the plan, the weight of the realization, and the actual costs of the project. The results obtained using Ms. Excel, are the BCWS, ACWP, and BCWP values ​​in the 40th week are Rp. 3,088,884,893, Rp. 2,850,876,747, and Rp. 2,802,698,381. In addition to these variables, there are also variables of the Earned Value method for costs and time. The results of the calculation of project performance variables against costs obtained CV, CPI, ETC, and EAC values ​​in the 40th week were -Rp. 49,178,366, 0.983, Rp. 483,789,304, and Rp. 3,334,666,051. These results indicate that the project experienced cost overruns based on the calculations made. Project performance variables against time obtained SV, SPI, ETS, and EAS values ​​of -Rp.287,186,512, 0.91, 5.50  6 weeks, and 46 weeks. These results indicate that the project experienced a delay of ± 1 week from the planned schedule.